Breakfast skipping and associated factors among Jordanian university students - Enas Alshdifat; Abdullah Alkhawaldeh; Mohammed Albashtawy; Wafa'a Ta'an; Khitam Mohammad; Sami Al-Rawashdeh; Malakeh Malak; Hanan Al-Modallal; Tariq Al-Dwaikat; Ma'en Aljezawi; Shereen Hamadneh; Mohammad Suliman; et al. (Wolters Kluwer Medknow Publications, 2024)
Background: Although breakfast skipping among university students is a significant concern, its prevalence and the contributing factors among university students have received little attention in the literature. This study aims to determine the prevalence of skipping breakfast among Jordanian university students and examine the associated factors and variations in rates of skipping breakfast by day of the week. Materials and Methods: A cross-sectional study was conducted among undergraduate students between March and May 2022 through a self-questionnaire. A convenience sample of 891 students was chosen at four Jordanian public universities. The data were analyzed using descriptive and inferential statistics. Results: The prevalence of skipping breakfast among university students was 66%. The reasons for skipping breakfast were having no time due to oversleeping and having no feeling of hunger (59% for both), followed by having no energy to prepare the breakfast and making no difference (49% and 48%), and not being able to afford to eat or buy breakfast (19%). There is a strong correlation between eating fast food and skipping breakfast. With whom the student eats breakfast is significantly associated with breakfast skipping, revealing that the highest percentages of skipping occur with friends. About 63% of students skipped breakfast through university days compared with 37% on the weekend, while 37% of them had breakfast through university days compared with 67% on the weekend. Conclusions: A high percentage of university students in Jordan skip breakfast. More attention should be paid to correlating factors and developing interventions to help students adhere to the breakfast.